# Problem: You may want to reference(Pages 183 - 186)Section 5.6 while completing this problem.Given the following data:N2(g) +  O2(g) →  2NO(g)           ΔH = + 180.72NO(g) + O2(g) → 2NO2(g)        ΔH = -113.12N2O(g) →  2N2(g) + O2(g)        ΔH = -163.2Use Hess's Law to calculate H for the following reaction:N2O(g) + NO2(g)  →  3NO(g)

###### FREE Expert Solution

(1) N2(g) +  O2(g) →  2NO(g)           ΔH = + 180.7

(2) 2NO(g) + O2(g) → 2NO2(g)        ΔH = -113.1

(3) 2N2O(g) →  2N2(g) + O2(g)        ΔH = -163.2

We shall modify the given reactions to arrive at the overall reaction. Any modification to the reaction is reflected in the value of ΔH for the reaction.

87% (183 ratings) ###### Problem Details

You may want to reference(Pages 183 - 186)Section 5.6 while completing this problem.

Given the following data:

N2(g) +  O2(g) →  2NO(g)           ΔH = + 180.7
2NO(g) + O2(g) → 2NO2(g)        ΔH = -113.1
2N2O(g) →  2N2(g) + O2(g)        ΔH = -163.2

Use Hess's Law to calculate H for the following reaction:

N2O(g) + NO2(g)  →  3NO(g)